Therapeutic treatment according to the Bobath concept based on the International Classification ICF in a patient after a stroke - case report - Lewandowska, Anna; Ratuszek-Sadowska, Dorota; Stępowska, Justyna; Kuczma, Monika; Kurczewski, Mikołaj; Hagner, Wojciech (Journal of Education, Health and Sport, 2018)
Neurological therapy of the patients after stroke is mainly aimed at the greatest possible growth of the function. During the treatment there are various techniques according to Bobath concept designed to inhibit pathological movement patterns, as well as the stimulation of a physiological response. The aim of this paper is to discuss, on the basis of the presented case, rehabilitation methods of patient after ischemic stroke of the right hemisphere. The physiotherapy examination, based on the International Classification of ICF, assessing problems in the body structures, functions and activities and participation, showed a weakness of the lower trunk muscles, pelvic floor and left hip, muscles hypotonia of directly occupied side, as well as increased muscle tension in left upper limb. Problems of patient activity levels were independent standing up and able to stand without help and lack of left upper limb function activity. Neurological therapy included the muscle tone normalization, work on strengthen core, left hip and pelvis muscles, priming the correct loading of the directly occupied side during the position changes from sitting position to standing and walking, as well as learning of daily living activities.